2024
DOI: 10.1093/rb/rbae038
|View full text |Cite
|
Sign up to set email alerts
|

Nano-hydroxyapatite promotes cell apoptosis by co-activating endoplasmic reticulum stress and mitochondria damage to inhibit glioma growth

Yifu Wang,
Hongfeng Wu,
Zhu Chen
et al.

Abstract: Despite a growing body of studies demonstrating the specific antitumor effect of nano-hydroxyapatite (n-HA), the underlying mechanism remained unclear. Endoplasmic reticulum (ER) and mitochondria are two key players in intracellular Ca2+ homeostasis and both require Ca2+ to participate. Moreover, the ER-mitochondria interplay coordinates the maintenance of cellular calcium homeostasis to prevent any negative consequences from excess of Ca2+, hence there needs in-depth study of n-HA effect on them. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…38 In another study, we also found that n HA could selectively inhibit glioma growth. 39 These data suggest that the released n HA from the composite membrane may have potential applications in the future for dural tissue healing and prevention of local tumor recurrence following glioma excision. Collectively, the combination of the rigidity and toughness of the biodegradable polymer PLCL and n HA is a promising idea for the development of a robust and biodegradable dura substitute, which has been rarely reported.…”
Section: Introductionmentioning
confidence: 84%
“…38 In another study, we also found that n HA could selectively inhibit glioma growth. 39 These data suggest that the released n HA from the composite membrane may have potential applications in the future for dural tissue healing and prevention of local tumor recurrence following glioma excision. Collectively, the combination of the rigidity and toughness of the biodegradable polymer PLCL and n HA is a promising idea for the development of a robust and biodegradable dura substitute, which has been rarely reported.…”
Section: Introductionmentioning
confidence: 84%